Treatment with β-blocker nebivolol ameliorates oxidative stress and endothelial dysfunction in tenofovir-induced nephrotoxicity in rats - Nascimento, Mariana Moura; Bernardo, Desiree Rita Denelle; de Bragança, Ana Carolina; Massola Shimizu, Maria Heloisa; Seguro, Antonio Carlos; Volpini, Rildo Aparecido; Canale, Daniele (Frontiers in Medicine, 2022)
Background: Tenofovir disoproxil fumarate (TDF), a widely prescribed component in antiretroviral regimens, has been associated with nephrotoxicity. Nebivolol is a third generation selective β-1 adrenergic receptor blocker and may protect renal structure and function through the suppression of oxidative stress and enhancement of nitric oxide (NO) synthesis. We aimed to investigate whether nebivolol could be an effective therapeutic strategy to mitigate tenofovir-induced nephrotoxicity. Methods: We allocated Wistar rats to four groups: control (C), received a standard diet for 30 days; NBV, received a standard diet for 30 days added with nebivolol (100 mg/kg food) in the last 15 days; TDF, received a standard diet added with tenofovir (300 mg/kg food) for 30 days; and TDF+NBV, received a standard diet added with tenofovir for 30 days and nebivolol in the last 15 days. Results: Long-term exposure to tenofovir led to impaired renal function, induced hypertension, endothelial dysfunction and oxidative stress. Nebivolol treatment partially recovered glomerular filtration rate, improved renal injury, normalized blood pressure and attenuated renal vasoconstriction. Administration of nebivolol contributed to reductions in asymmetric dimethylarginine (ADMA) levels as well as increases in endothelial nitric oxide sintase (eNOS) accompanied by renin-angiotensin-aldosterone system downregulation and decreases in macrophage and T-cells infiltrate. Furthermore, nebivolol was responsible for the maintenance of the adequate balance of thiobarbituric acid reactive substances (TBARS) and glutathione (GSH) levels and it was associated with reductions in NADPH oxidase (NOX) subunits. Conclusion: Nebivolol holds multifaceted actions that promote an advantageous option to slow the progression of kidney injury in tenofovir-induced nephrotoxicity.